Hubungan Pemahaman Konsep Pecahan dan Aturan Radd Dalam Ilmu Fara’idh terhadap Kemampuan Siswa dalam Menyelesaikan Masalah Pembagian Harta Warisan - Khaerul Iqbal Juhdi; Indah Nursuprianah; Muhamad Ali Misri (Holistik, 2017)
This study starts from the number of people around us who are still goingscience, fara'idh but the science is very important to be studied, understood and practiced especially among the Muslim community, but in reality both in our own neighborhood much practice division of inheritance is not based applicable law.Elderly ancient proverb says "learning at a time when parents like to carve on the water and learn to carve like a young diwaktu on rock". Therefore, this study was conducted on young people (students Manba'ul Huda MA) in order to determine the extent of students' knowledge and understanding of the concept of fractions andrules radd in resolving problems that are often overlooked by the Muslim community (the division of the inheritance).After conducting research with qualitative approach earned the average percentage of students answered a questionnaire by 72.43% to understanding the concept of fractions, 68.00% for the understanding of the rules radd, in the science fara'idh63.62% for the students' ability to resolve the matter of division inheritance. While the quantitative approach using t test analysis showed that there is a relationship X1 to Y with sig. amounted to 0.010 <0.05 andtcount> 2.717 ttable 2,023, there is no relationship X2 to Y with sig. amounted to 0.401> 0.05 and  valuet 0,849 <ttable 2.023. As to determine whether there is a relationship X1 and X2 to Y simultaneously researchers used F test, the results that there is a relationship X1 and X2 to Y simultaneously with sig. 0,001 <0.05 andFcount> 8.185 Ftable 3,23.